Gopabandhu’s Innovations and Experimentation in Educational Practices - Rout, Sarat Kumar (JOURNAL OF INDIAN EDUCATION, 2012)
Utkalmani Gopabandhu Das was a firm believer of God or Jagannathanism and his sacrifices and suffering for the cause of Swaraj testified to the remarkable saga of his selfless service to people, society and nation. To liberate people from all types of social evils, i.e. ignorance, blind belief, starvation and all forms of exploitation he started a social revolution by establishing Satyabadi Vanavidyalaya at Sakhigopal, eleven miles from Puri, on 12th August 1909, with nineteen students on the roll and himself as the Secretary along with a group of young Oriya scholars namely Pandit Gopabandhu Das, Acharya Harihar Das, Pandit Nilakantha Dash, Kripasindhu Mishra and Godavarish Mishra. The entire staff, under the inspiring leadership of Pandit Gopabandhu, was devoted to reconstructing the nation through education. Their philosophy of education was based on education for humanisation, open-air schooling, free and universal education, earning while learning, community-centred education, to achieve the objective of humanisation and completely developed personality by giving training to the mind and the body of the students. The school will be a beehive of active community-living and sustain co-operative effort. Thus he adopted an activity-centred curriculum for transaction of learning experiences. The teachers followed individualised instruction as per the needs of students which was very personal and cordial. A very healthy and intimate relationship developed between the teachers and the students in the Satyabadi School. The personal example of the teachers influenced the students for healthy personality development. The Satyabadi School provided an ideal training in self-discipline to the students. Students used to solve their problems in the “Boy’s own court.” The Satyabadi school hostel was organised on a novel plan with the aim of humanising the learning process.